Barriers to Co-Contribution in Superannuation: a Comparative Assessment of the Financial Benefits of Scheme Participation - Aaron Bruhn; Tim Higgins (Australasian Accounting, Business and Finance Journal, 2013)
Voluntary superannuation contributions provide a means for individuals to top-up their savings in a tax advantaged environment. In order to encourage voluntary contributions the government instituted the co-contribution scheme in 2003. Under the existing scheme, within a given financial year the government contributes up to a maximum of $500 when an individual on a low income makes a voluntary contribution of up to $1,000. Despite the apparent financial attractiveness of the scheme, participation among eligible persons is low. Reasons may include competing expenditure needs leading to a lack of sufficient funds for contribution, lack of trust in the system given regular changes to superannuation policy, and behavioural reasons including a short-term rather than long-term focus, procrastination from uncertainty and fear of regret, and loss aversion. In this paper we investigate another possible reason for low participation, namely poor financial opportunity cost. While an immediate 50% investment return may appear to be a ‘no-brainer’, for eligible individuals or families with mortgages, scheme participation may in fact not be optimal. We investigate the relative benefit of scheme participation versus reducing a mortgage, and conclude that while participation is sensible for those with short remaining mortgage terms, for those with longer mortgage terms the decision to participate may not be preferred unless one assumes generous long-term superannuation investment returns, or unless scheme participation is intended year on year for long durations.
Keywords: Superannuation; voluntary saving; co-contribution scheme; Barriers